Lighting-from-above prior in biological motion perception - Fedorov, Leonid A. (Sci Rep, 2018)
The visual system is able to recognize body motion from impoverished stimuli. This requires combining stimulus information with visual priors. We present a new visual illusion showing that one of these priors is the assumption that bodies are typically illuminated from above. A change of illumination direction from above to below flips the perceived locomotion direction of a biological motion stimulus. Control experiments show that the underlying mechanism is different from shape-from-shading and directly combines information about body motion with a lighting-from-above prior. We further show that the illusion is critically dependent on the intrinsic luminance gradients of the most mobile parts of the moving body. We present a neural model with physiologically plausible mechanisms that accounts for the illusion and shows how the illumination prior might be encoded within the visual pathway. Our experiments demonstrate, for the first time, a direct influence of illumination priors in high-level motion vision.